Religious Education Transformation in the Digital Era: A Comparative Study of Religiosity-Based School Implementation in Indonesia and Malaysia: (Transformasi Pendidikan Agama di Era Digital: Studi Komparatif Implementasi Sekolah Berbasis Religiusitas di Indonesia dan Malaysia) - Nur Saleha; Muhammad Abdillah Adli Dzil Ikram; Muhammad Azfar (Al Kautsar: Knowledge Advancements in Teaching Strategies and Research, 2024)
This comparative study examines the transformation of religious education in the digital era, focusing on implementation differences between Indonesia and Malaysia. Both countries have integrated digital technologies into Islamic education, yet face distinct challenges and policy approaches. In Indonesia, the adoption of online platforms and social media for religious instruction is growing, but limited infrastructure and unequal internet access hinder effectiveness, especially in rural areas. Malaysia, by contrast, has implemented more structured strategies through government-backed initiatives like DidikTV KPM and nationwide digital learning platforms, enhancing accessibility and teacher readiness. The findings highlight the crucial role of policy support, infrastructure readiness, and teacher training in optimizing digital religious education. This study contributes to the theoretical discourse on digital transformation in education and offers practical insights for policymakers seeking to enhance equitable and effective religious instruction in the 21st century.